Applicability of biological dye tracer in strip biosensor for ultrasensitive detection of pathogenic bacteria. (15th February 2019) - Bu, Tong; Huang, Qiong; Yan, Lingzhi; Zhang, Wentao; Dou, Leina; Huang, Lunjie; Yang, Qingfeng; Zhao, Bingxin; Yang, Baowei; Li, Tao; Wang, Jianlong; Zhang, Daohong
Highlights: Gram staining and direct immunoassay were first adopted for S. Enteritidis detection. The marking signal was derived from one-step bacteria staining with crystal violet. The device exhibited excellent sensitivity, simplicity, selectivity and feasibility. Results could be clearly distinguished by naked eyes even under a lower analyte level. Abstract: Here, a facile, label-free and sensitive lateral flow strip (LFS) biosensor for foodborne pathogens was established relying on the innovative introduction of Gram staining and the direct immunoreaction. Target bacteria can be directly marked with crystal violet (CV) by one-step staining which is superior to traditional signal marking techniques in LFS assay, and the method's selectivity can be guaranteed by high-specificity monoclonal antibody. With Salmonella Enteritidis ( S. Enteritidis) as a model target, this protocol can selectively detect 80 CFU mL −1 S. Enteritidis within 11 min in the optimized conditions. Moreover, with Listeria monocytogenes as another model target, the biosensor shows a high universality for detections of both gram-negative and gram-positive bacteria. The unexpected applicability of biological dye tracer in strip biosensor reveals that the biological dye can be a potential tool serving as a universal signal tracer for pathogenic microorganisms in food safety monitoring and early clinical diagnosis.